Effect of Iron Isomaltoside on Skeletal Muscle Energetics in Patients With Chronic Heart Failure and Iron Deficiency: FERRIC-HF II Randomized Mechanistic Trial. Issue 21 (21st May 2019) - Charles-Edwards, Geoffrey; Amaral, Nelson; Sleigh, Alison; Ayis, Salma; Catibog, Norman; McDonagh, Theresa; Monaghan, Mark; Amin-Youssef, George; Kemp, Graham J.; Shah, Ajay M.; Okonko, Darlington O.
Abstract : Background: Iron repletion augments exercise capacity in chronic heart failure (HF), but there is a lack of mechanistic data explaining how iron could augment exercise performance despite minimal changes in hemoglobin (Hb). Besides Hb, iron is an obligate component of mitochondrial enzymes that generate cellular energy in the form of adenosine triphosphate and phosphocreatine (PCr). Dynamic phosphorus magnetic resonance spectroscopy is a noninvasive tool that quantifies in vivo muscle energetics by measuring the kinetics of PCr recovery after exertion. We tested the hypothesis that intravenous iron repletion in chronic HF enhances skeletal muscle energetics as reflected by shorter PCr recovery half-times (PCr t 1/2 ) on phosphorus magnetic resonance spectroscopy. Methods: We enrolled 40 patients (50% anemic) with chronic HF, New York Heart Association class ≥II, left ventricular ejection fraction ⩽45%, and iron deficiency (ferritin<100 μg/L or 100–300 μg/L with transferrin saturation <20%). Subjects underwent stratified (anemic versus nonanemic) randomization (1:1) to a single, double-blinded, total dose infusion of iron isomaltoside or saline placebo with end points reassessed early at 2 weeks posttreatment to minimize confounding from exercise adaptation. The primary end point was PCr t 1/2 at 2 weeks. Secondary end points included ADP recovery half-time (ADP t 1/2; energetic marker), iron status, symptoms, Hb, exercise capacity, and safety. Results: In the total population, treatment groups were similar at baseline. At 2 weeks, iron isomaltoside improved PCr t 1/2 (adjusted difference, –6.8 s; 95% CI, 11.5 to –2.1; P =0.006), ADP t 1/2 (–5.3 s; 95% CI, –9.7 to –0.9; P =0.02), ferritin (304 ng/mL; 95% CI, 217–391; P <0.0001), transferrin saturation (6.8%; 95% CI, 2.7–10.8; P =0.002), New York Heart Association class (–0.23; 95% CI, –0.46 to –0.01; P =0.04), resting respiratory rate (–0.7 breaths/min; 95% CI, –1.2 to –0.2; P =0.009), and postexercise Borg dyspnea score (–2.0; 95% CI, –3.7 to –0.3; P =0.04), but not Hb (2.4 g/L; 95% CI, –3.5 to 8.4; P =0.41). Adverse events were similar between groups. In subgroup analyses, iron isomaltoside improved PCr t 1/2 in anemic (–8.4 s; 95% CI, –16.7 to –0.2; P =0.04) and nonanemic (–5.2 s; 95% CI, –10.6 to 0.2; P =0.06) cohorts. Conclusions: In patients with chronic HF and iron deficiency, a total repletion dose of iron isomaltoside given at a single sitting is well tolerated and associated with faster skeletal muscle PCr t 1/2 at 2 weeks, implying better mitochondrial function. Augmented skeletal muscle energetics might therefore be an important mechanism via which iron repletion confers benefits in chronic HF despite minimal Hb changes. Clinical Trial Registration: URL: https://www.clinicaltrialsregister.eu/ctr-search/trial/2012-005592-13/GB . Unique identifier: EudraCT 2012-005592-13. Abstract : Supplemental Digital Content is available in the text.